Forest fire hazard and risk in Colorado - Ryan, Kevin C., author; Barrows, Jack S., advisor; Mogren, E. W., committee member; Fosberg, Michael A., committee member (Colorado State University. Libraries, 1976)
The purpose of the study was to enhance understanding of forest fire hazard and risk factors which are important to resource management and public safety. Annual forest fire records were used to determine general trends in forest fire occurrence from 1946 to 1973 for the State of Colorado and the ten National Forests in Colorado. Five year moving averages were used to determine trends in the number of fires and acres burned. The trend in man caused fires was compared to population trends to determine the effect of recent growth on fire occurrence. Individual fire reports from the ten National Forests were used for detailed analysis of fire occurrence from 1 960 to 1973. Analysis concentrated on the cause of fire, forest cover type at origin of fire, aspect and slope steepness. Seasonal patterns of fire occurrence were also determined. The number of fires, acres burned, average size per fire, number of class C and larger fires (over 10 acres), and percent of class C and larger fires were computed for all variables analyzed in the study. A conceptual model of forest fire potential was used to combine hazard and risk in the forest cover types and elevation zones. The number of fires, acres burned, and number of class C and larger fires were calculated on a per million acre basis and normalized on a scale from Oto 100. The normalized numbers of fires, acres burned, and class C and larger fires were used respectively as ignition, magnitude, and spread potentials. Combined they provided the total fire potential for the cover types and elevation zones. Results indicate a definite increasing trend in both lightning and man caused fires in Colorado. Man caused fires approximately tripled during the 28 year period while population only doubled. Lightning and man caused fires also increased in the National Forests but at a much slower pace than in the State. Although fires were more common in the high risk months of July and August, hazard is generally lower than in the spring and fall months. The majority of large fires burned in June and October. The forest cover type, elevation and aspect strongly affect ed patterns of fire occurrence. The ponderosa pine had the greatest number of fires and acres burned. The number of class C and larger fires was highest in the grass and sagebrush type. Man caused ignitions per acre were highest in the lower elevations while lightning ignitions were highest in the middle elevations. Both lightning and man caused ignitions per acre were low above 8,500 feet. Aspect also had a strong effect on fire occurrence. Southerly exposures had more and larger fires than northerly ones.
Covers not scanned.
Keywords: Forest fires -- Colorado